Product Rule for Derivatives/Examples/2 a x times Exponential of a x^2

From ProofWiki
Jump to navigation Jump to search

Examples of Use of Product Rule for Derivatives

$\map {\dfrac \d {\d x} } {2 a x e^{a x^2} } = 2 a e^{a x^2} \paren {1 + 2 a x^2}$


Let $u = 2 a x$.

Let $v = e^{a x^2}$.

Thus we have:

$y = u v$

and so:

\(\ds \dfrac {\d y} {\d x}\) \(=\) \(\ds v \dfrac {\d u} {\d x} + u \dfrac {\d v} {\d x}\) Product Rule for Derivatives
\(\ds \) \(=\) \(\ds e^{a x^2} \cdot 2 a + 2 a x \cdot \paren {2 a x e^{a x^2} }\) Power Rule for Derivatives, Derivative of $e^{a x^2}$
\(\ds \) \(=\) \(\ds 2 a e^{a x^2} \paren {1 + 2 a x^2}\) simplification